مسح لطفيليات القناة الهضمية لأبقار محطة الفيحاء في محافظة بابل - سوادي, هشام عطوان (University of Thi-Qar Journal of Science, 2014)
The present study was achieved during the period September 2009 – Jane 2010 to detected parasitic infection in digestive tract among cows rearing at Al-Fyha station in Babylon province. Daring the above period, a total of 82 faecal samples were collected from cows aged 0.5-5 years, these sample were examined directly by iodine tincture and flotation by using Zink sulfate to detected protozoa (trophozoites and cysts) and worm eggs. The result of the study exhibited that the detected parasites in digestive track of cows was protozoa only, the rate of infection with Giardia parasite was 25.60 %, while it was 29.26 % with coccidiosis